2001
DOI: 10.2105/ajph.91.6.959
|View full text |Cite
|
Sign up to set email alerts
|

Gonorrhea in the HIV era: a reversal in trends among men who have sex with men

Abstract: A B S T R A C TObjectives. Gonorrhea cases among men who have sex with men (MSM) declined in the early years of the HIV epidemic. We evaluated more recent trends in gonorrhea among MSM through the Centers for Disease Control and Prevention's Gonococcal Isolate Surveillance Project.Methods. Isolates and case information were collected from 29 US sexually transmitted disease (STD) clinics. Gonococcal urethritis cases among MSM were compared with those among heterosexual men, and cases among MSM in 1995 to 1999 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Epidemiologic data in North Carolina indicates that among some subgroups of gay university students, HIV incidence and prevalence may be as high as 14% and 32%, respectively (Anonymous, 2004; Miller et al, 2002). Recent studies also have observed increasing incidence rates of STDs among gay men in the US (CDC, 1999, 2001; Fox et al, 2001; Williams et al, 1999). In our study, the higher number of partners among gay men is challenging to interpret because gay men reported more multiple sexual partners but not significantly different condom use consistency.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic data in North Carolina indicates that among some subgroups of gay university students, HIV incidence and prevalence may be as high as 14% and 32%, respectively (Anonymous, 2004; Miller et al, 2002). Recent studies also have observed increasing incidence rates of STDs among gay men in the US (CDC, 1999, 2001; Fox et al, 2001; Williams et al, 1999). In our study, the higher number of partners among gay men is challenging to interpret because gay men reported more multiple sexual partners but not significantly different condom use consistency.…”
Section: Discussionmentioning
confidence: 99%
“…Since its inception GISP has provided valuable information that has been used to update the CDC’s Sexually Transmitted Diseases (STD) Treatment Guidelines as well as provided data used by CDC to modify the treatment recommendations for gonorrhea in real time. For example, data from GISP was pivotal in alerting public health officials about the increasing prevalence of gonorrhea among MSM in the late 1990’s (125), the recommendation to avoid the use of fluoroquinolones among MSM with gonorrhea in 2004 (75) and, in 2007, the recommendation that fluoroquinolones should not be used for any patient that presents with gonorrhea, leaving ESCs as the only remaining class of antimicrobials recommended for treatment of gonorrhea (126). Furthermore, in 2010, due to concerns regarding emergence of ESC resistance CDC introduced recommendations for dual antimicrobial therapy.…”
Section: Gonococcal Isolate Surveillance Project (Gisp) – An Example mentioning
confidence: 99%
“…Men who have sex with men (MSM) are at high risk of acquiring sexually transmitted diseases (STDs) relative to non-MSM in the United States, and STD incidence is increasing among U.S. MSM (Beltrami, Shouse, & Blake, 2005; Centers for Disease Control and Prevention [CDC], 1997, 1999, 2001, 2002, 2006; Ciesielski, 2003; K. K. Fox et al, 2001).…”
mentioning
confidence: 99%